Penggunaan Media Game Wordwall Sebagai Upaya Meningkatkan Keaktifan Siswa dalam Pembelajaran Al Qur'an dan Hadits: Meningkatkan Keaktifan Siswa Kelas VIII MTs Darul Amin dalam Pembelajaran Al-Qur'an dan Hadits Menggunakan Media Wordwall - Aminaty, Diny; Jasiah, Jasiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2024)
This research aims to describe the use of Wordwall learning media in increasing student activity in learning the Al-Qur'an and Hadith in class VIII MTs Darul Amin Palangka Raya. This research uses a qualitative descriptive method with data collection techniques in the form of interviews, observation, documentation and questionnaires. The results of using Wordwall media involved 24 students and showed a very positive response. As many as 100% of students felt that learning was more interesting and less boring, and 95.8% of students felt happy using Wordwall. In addition, 91.7% of students stated that they wanted to use Wordwall again in the next lesson, and 83.3% of students believed that this media helped them understand the material better. Wordwall media has been proven to increase student participation in group discussions, motivate them to ask questions, and facilitate problem solving exercises. Thus, Wordwall can be an innovative solution for creating an interactive and fun learning atmosphere. Teachers are expected to be able to apply this media on an ongoing basis to support more effective learning and according to students' needs.